KEKUATAN SURAT BUKTI PERKAWINAN YANG DILANGSUNGKAN DI LUAR INDONESIA SETELAH DIDAFTARKAN DI KANTOR CATATAN SIPIL - Isetyowati Andayani (Perspektif, 2005)
Strength of bill of evidence of marriage which is passed off outside Indonesia have the perfect legal force, that matter as according to appliance of letter evidence representing one of verification in scope of relation to court of justice. In the case of happened the divorce can be brought to trial country in region in Indonesia.